2012
DOI: 10.1002/cphc.201200501
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Reduced Graphite Oxide Sheets with a Zwitterionic Surfactant

Abstract: Films of a few layers in thickness of reduced graphite oxide (RGO) sheets functionalized by the zwitterionic surfactant N-dodecyl-N,N-dimethyl-3-ammonio-1-propanesulfonate (DDPS) are obtained by using the Langmuir-Blodgett method. The quality of the RGO sheets is checked by analyzing the degrees of reduction and defect repair by means of X-ray photoelectron spectroscopy, atomic force microscopy (AFM), field-emission scanning electron microscopy (SEM), micro-Raman spectroscopy, and electrical conductivity measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 78 publications
(151 reference statements)
4
45
0
Order By: Relevance
“…The clear advantage of this method is the possibility of tuning the interface assembly by adjusting the surface pressure of the Langmuir monolayer by compressing or expanding the film using barriers 22. 23 Consequently, it offers the possibility of preparing reproducible films of polymers,24 surfactants25 and nanoparticles2628 with the control over interparticle distance necessary to exploit the materials in technological applications. In the case of GO sheets, the air–water interface forces them to lay flat, so that the assemblies can be transferred onto solids by the LB technique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clear advantage of this method is the possibility of tuning the interface assembly by adjusting the surface pressure of the Langmuir monolayer by compressing or expanding the film using barriers 22. 23 Consequently, it offers the possibility of preparing reproducible films of polymers,24 surfactants25 and nanoparticles2628 with the control over interparticle distance necessary to exploit the materials in technological applications. In the case of GO sheets, the air–water interface forces them to lay flat, so that the assemblies can be transferred onto solids by the LB technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of GO sheets, the air–water interface forces them to lay flat, so that the assemblies can be transferred onto solids by the LB technique. Therefore, it has been successfully used to deposit graphite oxide2932 and surfactant‐functionalized and non‐functionalized RGO 33. Note that several conditions must be fulfilled to build self‐assembled particle monolayers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shukla et al [31] reported a fast and inexpensive method to the synthesis of single- or few-layer graphene by cleaving off the bulk graphite on the substrate made of borosilicate glass or any insulating materials with ionic conductivity, which has promise for industrial level production for certain engineering applications. Martín-García et al [32] showed that reduced GO functionalized zwitterionic surfactant can significantly improve the electrical conductivity of graphene film, thereby enhancing its quality. Obraztsov et al [33] employed chemical vapor deposition (CVD) to synthesize graphene on a Ni substrate and found that a few graphene layers with thickness ranging from 1 to 2 nm grew successfully on the surface of the substrate, while the same approach failed to make the graphene adhere to a Si substrate, ascribed to the large lattice incompatibility between silicon and graphite.…”
Section: Synthesis and Analysis Of Graphene-based Materialsmentioning
confidence: 99%
“…An empirical formula shows that L a is inversely proportional to I D / I G . Not only the I D /I G ratio, but also the D and G band positions and linewidths can provide the information on the size and structural evolution of carbon materials such as carbon fibers and graphene …”
Section: Introductionmentioning
confidence: 99%